First Nations’ Equity Experts Talking about Differential Treatment, Identity Tension and Cultural Sovereignty: An Application of Weber’s Sociology - Sedgwick, Brenda Maureen (2015)
Service providers, researchers and policy makers acknowledge that First Nations, and other marginalized citizens, encounter disproportionate barriers to being heard, feeling respected, developing trust, and accessing care that is appropriate. People experience differential treatment and related feelings; although there are laws, policies, and values to prohibit discrimination and bias. By way of examining and explaining differential treatment, social science refers to micro-inequities, multiple oppressions, entrenched colonialism and divisive social structures. The thesis enters into this scholarly dialogue to consider input by more than 100 First Nations equity experts. The thesis applies a Weberian approach in sociology as a method to gather information and as a lens to examine the concerns that participants raise. The student’s interest to gather perspectives on a new framework in health studies, known as ‘cultural safety,’ was the starting point for the thesis. In particular, the student was interested to know the meaning and implications of cultural safety to First Nations people in Northern Ontario who have first-hand experience with marginalization in health delivery organizations. Prior to ethical approval, the student developed questions by way of engaging with 79 individuals in her personal, community (grassroots), professional, and academic networks. Questions to individuals and focus groups asked about seven focal points. These points of interest were culture, Anishnawbe culture, cultural difference and sameness, how culture maps onto identity, cultural safety, factors that negatively and positively influence cultural safety, and optimal healing environments. An optimal healing environment was prior defined by the student, to participants, as one that is equitable and keeps a person’s identity and culture intact and unthreatened. Upon ethical approval in July 2013 by the Lakehead University Research Ethics Board (REB), the student asked a sequence of questions to132 interview and conversation discussants. Individual and group discussions, between August 2013 and February 2015, raised concern with differential treatment as a factor influencing identity (causing tension), cultural sovereignty (imposing on culture), and organizational environments (suboptimum conditions for healing). The thesis project exemplifies using Weber’s ideal type methodology. A Weberian approach in sociology prioritizes using the words and meanings that people themselves use to explain their experiences and contexts. Using techniques of constant comparison and reduction; the student organizes the words by First Nations equity experts into a solution to the concerns they raise. Identity tension is put forward as a concept to describe a human outcome of differential treatment. Mutual respect is suggested as a transformative concept to reflect an encompassing theme. Mutual respect typology is described as a way of being, knowing and doing, using the words of First Nations equity experts who participated in the thesis based on their first-hand experience with marginalization. The thesis emerges a hypothesis for future consideration that mutual respect may moderate (but does not necessarily solve or eliminate) the problem (paradox) of identity tension. A next qualitative research step would be further defining mutual respect from the perspective of diverse people with power and privilege, but no first-hand knowledge of what it is like to be and feel marginalized. Another outcome of the thesis is the emergence of a mixed methods questionnaire. The questionnaire, readied for further field testing, is an opportunity to gather information that can later be rendered by way of factor analysis. Factor analysis is a statistical technique which would assist further clarifying and specifying the dimensions of mutual respect.